2013
DOI: 10.1093/schbul/sbt197
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Reward Processing and Motivational Impairment in Schizophrenia

Abstract: This article reviews and synthesizes research on reward processing in schizophrenia, which has begun to provide important insights into the cognitive and neural mechanisms associated with motivational impairments. Aberrant cortical-striatal interactions may be involved with multiple reward processing abnormalities, including: (1) dopamine-mediated basal ganglia systems that support reinforcement learning and the ability to predict cues that lead to rewarding outcomes; (2) orbitofrontal cortex-driven deficits i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
301
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(327 citation statements)
references
References 104 publications
16
301
2
1
Order By: Relevance
“…While auto-activation deficits are primarily observed in patients with basal ganglia lesions, compelling evidence points to motivational deficits in schizophrenia patients with apathy (for a recent review see Strauss, Waltz, & Gold, 2014). Option generation is a cognitive process occurring in a predecisional stage.…”
Section: Apathy As a Deficit In Option Generationmentioning
confidence: 99%
“…While auto-activation deficits are primarily observed in patients with basal ganglia lesions, compelling evidence points to motivational deficits in schizophrenia patients with apathy (for a recent review see Strauss, Waltz, & Gold, 2014). Option generation is a cognitive process occurring in a predecisional stage.…”
Section: Apathy As a Deficit In Option Generationmentioning
confidence: 99%
“…Motivational deficits, which are understood under the broader umbrella of negative symptoms 1 , are a core feature of schizophrenia and have important consequences for treatment response 2 . For example, previous research 3 demonstrated that negative symptoms cause people with schizophrenia to be disinterested in physical activity and exercise programmes.…”
Section: Introductionmentioning
confidence: 99%
“…There was no observable impairment on a behavioural level. This may indicate no motivational deficits in SZ however it does not account for the dysfunctions found on a neural level [17]. Therefore, possible neuro-functional impairments of social and monetary reward processing should be investigated further.…”
Section: Discussionmentioning
confidence: 97%
“…The low activation during reward anticipation was associated with greater negative symptom severity [17]. Furthermore, patients appear to show inappropriately strong activations in reward-associated brain areas in response to neutral stimuli as compared to healthy controls [23,25].…”
Section: Reward Processing In Schizophreniamentioning
confidence: 87%
See 1 more Smart Citation